2012
DOI: 10.22201/icat.16656423.2012.10.6.344
|View full text |Cite
|
Sign up to set email alerts
|

FSM State-Encoding for Area and Power Minimization Using Simulated Evolution Algorithm

Abstract: In this paper we describe the engineering of a non-deterministic iterative heuristic [1] known as simulated evolution(SimE) to solve the well-known NP-hard state assignment problem (SAP). Each assignment of a code to a state isgiven a Goodness value derived from a matrix representation of the desired adjacency graph (DAG) proposed byAmaral et.al [2]. We use the (DAGa) proposed in previous studies to optimize the area, and propose a new DAGpand employ it to reduce the power dissipation. In the process of evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Inspired by the theory of evolution, the algorithm has several distinctive features as mentioned in Section 1. Despite its distinctive features and excellent performance, the algorithm and its hybrid variants have received little attention from researchers in some domains such as healthcare [31], internet traffic engineering [18], network design optimization [6,32], microelectronics [33][34][35], and cloud computing [17,36,37].…”
Section: Basic Simulated Evolution Algorithmmentioning
confidence: 99%
“…Inspired by the theory of evolution, the algorithm has several distinctive features as mentioned in Section 1. Despite its distinctive features and excellent performance, the algorithm and its hybrid variants have received little attention from researchers in some domains such as healthcare [31], internet traffic engineering [18], network design optimization [6,32], microelectronics [33][34][35], and cloud computing [17,36,37].…”
Section: Basic Simulated Evolution Algorithmmentioning
confidence: 99%
“…Through using this method, a set of non-dominated solutions can be obtained at the cost of a long evolutionary time. Sait et al used simulated evolution algorithm (SimE) [18] to solve the problem by combining the area and power objectives, and SimE heuristic produced better quality results in most cases, and/or in lesser time, when compared to both deterministic heuristics and non-deterministic iterative heuristics.…”
Section: Related Workmentioning
confidence: 99%
“…Khan comprehensively studied state assignment methods for power minimisation of FSMs. GA and Tabu‐search are utilised as search space exploration tools in searching for lower area and power solutions [18]. It concluded that cost saving can be achieved by using a more accurate cost measure, but come with more computational time.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations